Combinatorial Interpretation of General Eulerian Numbers. (2nd January 2014) - Xiong, Tingyao; Hall, Jonathan I.; Tsao, Hung-Ping
Abstract : Since the 1950s, mathematicians have successfully interpreted the traditional Eulerian numbers andq -Eulerian numbers combinatorially. In this paper, the authors give a combinatorial interpretation to the general Eulerian numbers defined on general arithmetic progressionsa, a + d, a + 2 d, … .